Transition-Metal-Free Approach for the Synthesis of N-Arylated Piperidones and their Ketals from Ketene Dithioacetals - Sahu, Satya Narayan; Shaw, Ranjay; Althagafi, Ismail; Pratap, Ramendra (Synlett, 2024)
N-Arylated piperidones are present as pharmacophores in many pharmaceuticals and serve as useful precursors for the construction of important new molecules. We have developed a transition-metal-free, cost-effective, and mild approach for the synthesis of N-(hetero)arylated piperidones and their ketals by using ketals of piperidones and 2-oxo-5,6-dihydro-2H-benzo[h]chromene-3-carbonitriles as precursors. The desired products were obtained in two steps: amination of the 2-oxo-5,6-dihydro-2H-benzo[h]chromene-3-carbonitrile from piperidone, followed by ring transformation using a suitable nucleophile source. We have successfully tethered functionalized dihydrophenanthrenes, hydrobenzo[c]phenanthrenes, and benzoquinolines to piperidinone moieties under transition-metal-free conditions.
Keywords: ketene dithioacetals; piperidone; dihydrophenanthrenes; chromenes; ring transformation; cyanoacetamides